2018
DOI: 10.1080/08039488.2018.1441906
|View full text |Cite
|
Sign up to set email alerts
|

Thiol/disulphide homeostasis in schizophrenia patients with positive symptoms

Abstract: The disulfide/native thiol ratio in patients with schizophrenia who have been using medication for the last 2 months has been found to be significantly higher than controls who have not been using medication, may be indicating that the level of native thiol does not increase in a correlation as high as the increase in disulfide levels. It demonstrates that thiol/disulfide equilibrium has shifted towards the disulfide. The excess disulfide amounts might associated with both disease itself and the using medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Previous studies researched thiol-disulphide homeostasis in many other acute and chronic diseases [ 20 22 ]. However, there has been no study researching thiol/disulphide homeostasis in pediatric patients with AKI using a new, automated method [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies researched thiol-disulphide homeostasis in many other acute and chronic diseases [ 20 22 ]. However, there has been no study researching thiol/disulphide homeostasis in pediatric patients with AKI using a new, automated method [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there is growing interest in thiol-disulphide homeostasis test. The many diseases .have been associated with a deterioration in thiol-disulphide homeostasis, such as Alzheimer's disease, Parkinson's disease, schizophrenia, coronary artery disease, acute myocardial infarction, pneumonia, acute pancreatitis, ankylosing spondylitis, and age-related macular degeneration [8,9,18,19]. Thiol compounds forming an important part of the antioxidant defense system are vulnerable to oxidant agents [20].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the lack of H 2 S production may cause the pathology of Parkinson's disease, Huntington's disease and Alzheimer's disease (Cao et al, 2018;Chung et al, 2004;He et al, 2016;Paul et al, 2014;Sbodio et al, 2016Sbodio et al, , 2018Vandiver et al, 2013;Wright et al, 2016;Xie et al, 2013). The detrimental effects caused by the excess production of H 2 S and H 2 S n (Ide et al, 2019) as well as those by lacking in the neuroprotective effect of these molecules (Topcuoglu et al, 2017;Ünal et al, 2018;Xiong et al, 2018) have been reported for the pathogenesis of schizophrenia. (Taub et al, 1999).…”
Section: Pathophysiological Role Of H 2 S H 2 S N and Nomentioning
confidence: 99%